A Highly Efficient Eu2+ Excited Phosphor with Luminescence Tunable in Visible Range and Its Applications for Plant Growth. Issue 22 (12th September 2021) - Kang, Ziyong; Wang, Shichuan; Seto, Takatoshi; Wang, Yuhua
Abstract: A series of Rb x K2− x CaPO4 F:Eu 2+ phosphors are synthesized using a high‐temperature solid‐phase method. An increase in the Rb + concentration leads to the Eu 2+ ‐excited phosphor emission spectra being shifted from red to cyan. Interestingly, the excitation spectrum does not exhibit any variations, which indicates the possibility of mixing the red (Rb0.2 K1.8 CaPO4 F:Eu 2+ ) and cyan (Rb2 CaPO4 F:Eu 2+ ) phosphors for plant growth. This luminescence tuning is attributed to the substitution of K + with Rb +, which produces an inferior crystal‐field splitting that increases the energy at the lowest 5d level, and enhances the rigidity of the crystal structure, which results in a gradual decrease in the Stokes shift and a consequent blue shift in the emission spectrum. Time‐resolved photoluminescence emission spectroscopy further confirms the occurrence of broadband emission owing to the occupation of multiple sites by Eu 2+ . Light‐emitting devices appropriate for plant growth are fabricated by mixing the two phosphors with a 380‐nm UV chip, and a light‐conversion film is prepared using the red phosphor and PDMS glue. The Chlorella‐based plant growth experiment reveals that the growth rate of Chlorella is 12.2% higher than that of the blank group, indicating the favorable effect of the light‐conversion film on plant growth. Abstract : Red and cyan phosphors (Rb0.2 K1.8 CaPO4 F:Eu 2+ and Rb2 CaPO4 F:Eu 2+ ) are mixed to satisfy both blue and red light requirements for plant photosynthesis. A light‐emitting diode and light‐conversion film are fabricated, and an outdoor chlorella growth experiment is carried out. Experimental results proved that the investigated phosphor is an ideal light‐conversion material, and the fabricated film can be used for outdoor plant cultivation.